Validation of lethality processes for products with slow come up time: Bacon and bone-in ham. (October 2019) - Sindelar, J.; Glass, K.; Hanson, R.; Sebranek, J.G.; Cordray, J.; Dickson, J.S.
Abstract: Pork bellies and boneless hams were smoked or cooked using unusually long processes to determine the impact of extended come-up times on the populations of Clostridium perfringens, Salmonella enterica, Staphylococcus aureus and Listeria monocytogenes . The products were formulated using brine formulations representative of what might be used in commercial production, and the thermal processes were more than doubled in length. Pork bellies and boneless hams were inoculated on the surface as well as 1 cm below the surface, and samples were collected every 3 h. The populations of C. perfringens (spores and vegetative cells) at internal locations of pork bellies increased by less than 1 log10 and declined significantly (approximately 3 log10 /cm 2 ) on the surface of the bellies during an extended bacon process. The populations of S. enterica, L. monocytogenes and S. aureus did not increase during the extended bacon process. The populations of C. perfringens (spores and vegetative cells), S. aureus, S. enterica and L. monocytogenes declined significantly over an extended ham process. There were significant population reductions (>2 log10 /cm 2 ) at 7 h (surface) and 12 h (>5 log10 /g; internal) for the hams. Populations of both surface and internal locations of the hams declined to a point approaching the limit of detection of the assays within 17 h. Highlights: C. perfringens increased by less than 1 log10 during an extended bacon process. S. enterica and S. aureus did not increase during an extended bacon process. L. monocytogenes did not increase during an extended bacon process. Populations of C. perfringens declined significantly during an extended ham process. The other bacterial pathogens declined significantly during an extended ham process.